Assessment of drug-related problems among breast cancer patients in a cancer specialty center in Nepal - Aman Kumar Sah; Roshan Prajapati; Nabin Pathak; Sushil Panta; Shila Gurung (PLoS ONE, 2025)
Introduction Breast cancer is the leading cancer among women globally, and its management typically involves surgery, radiotherapy, and chemotherapy. This combination of complex treatment increases the risk of drug-related problems (DRPs), which can negatively impact the quality of life as it prolongs the hospital stays, increases healthcare costs, and leads to morbidity and mortality. Research on DRPs in the context of breast cancer patients in Nepal is limited; therefore, this study aimed to identify DRPs, assess their prevalence, and examine their associated factors, while emphasizing the importance of pharmaceutical care. Methods A cross-sectional study was conducted at Bhaktapur Cancer Hospital, Nepal, from February to May 2024. The medical records of 92 patients were reviewed to identify DRPs using the Pharmaceutical Care Network Europe V9.1 tool, along with related scientific literatures and evidence-based guidelines, and verified by two independent medical oncologists. Descriptive statistics were used to summarize the patient characteristics, while the chi-square test was used to evaluate the associations between socio-demographic and clinical characteristics with the presence of DRPs, with a p-value <0.05 considered statistically significant. Results DRPs were identified in 91 of 92 patients (98.9%), totaling 104 events. Most DRPs (87.5%) concerned treatment safety, while 12.5% involved treatment effectiveness. Patient-related factors (43.4%) and drug selection (33.3%) were primary causes. Common adverse effects included alopecia (88.0%) and anorexia (84.8%). A significant association was observed between adverse drug reactions (ADRs) and DRPs (Fisher’s exact p-value = 0.011). Conclusion DRPs were highly prevalent among breast cancer patients, mainly due to safety issues, with ADRs significantly contributing to it. Findings highlight the need for larger multicentric and cohort studies, and integration of oncology pharmacy services to optimize pharmaceutical care and minimize DRPs.